Antibacterial/Antiviral Face Masks: Processing, Characteristics, Challenges, and Sustainability (MIST International Journal of Science and Technology, 2023)
The face mask has become a part of our daily life after the emergence of SAR-CoV-2, commonly known as the novel coronavirus 2019 or, COVID-19 all over the world. On a day-to-day basis, previously the face mask has been used to filter airborne particles entering the body and affecting the respiratory system, especially by individuals in pollution-prone areas. But as the pathogens having severe acute respiratory disease-causing abilities emerge with the potential to create a pandemic, the necessity of virus/bacteria killing ability along with the filtration efficiency of the face mask has come into account. Existing ordinary face masks have filtration capacity only. Sometimes it cannot restrict particles and pathogens of nano or even micro-scale. Moreover, when it is disposed of after use, it can be a potential source of pathogen transmission. Therefore, the development of antiviral/antibacterial face masks is the need of the hour. This article focuses on the advancement of face mask processing methods, existing and promising antibacterial/antiviral agents, socio-economic sustainability, and challenges in achieving the goal of a green environment. Besides, various characteristics of the face mask like swelling and degradation properties, morphologies (SEM, FESEM), mechanical strength, antioxidant property, and antimicrobial activity are also revealed. Lastly, some future perspectives and directives are accordingly discussed with the hope that the grim of any future pandemic should not shroud us and make the world stalled again.MIJST, Vol. 11, December 2023 : 61-79DOI: https://doi.org/10.47981/j.mijst.11(02)2023.421(61-79)